Analysis of the Acceptance Factor of Android-Based Parking Information Systems in Indonesia - Romi Ilham; Nanang Shonhadji; Hariadi Yutanto; Diah Ekaningtyas (Communications - Scientific letters of the University of Zilina, 2020)
Parking is an unrelenting problem, with more vehicles having an impact on the way how to park a vehicle. Some experts have made various breakthroughs in overcoming parking problems; one of them is using smartphone technology as a system to facilitate the way to park. This study aims to analyse user acceptance using the Unified Theory of Acceptance and Use of Technology UTAUT method with structural equation models (SEM-PLS), against 221 respondents. The result is that performance expectations, effort expectancy, and social influence variables have a significant effect on behavioural intention. Then the facilitating conditions variable and behavioural intention significantly influence the use of behaviour for using smartphone parking systems. Furthermore, this research is expected to help the government to find out what factors affect the parking system.